Fluctuation-dissipation in thermoelectric sensors. (1st January 2023) - Tran, N. A. M.; Dutt, A. S.; Pulumati, N. B.; Reith, H.; Hu, A.; Dumont, A.; Nielsch, K.; Tremblay, A.-M. S.; Schierning, G.; Reulet, B.; Szkopek, T.
Abstract: Thermoelectric materials exhibit correlated transport of charge and heat. The Johnson-Nyquist noise formula 4 k B T R for the spectral density of voltage fluctuations accounts for fluctuations associated solely with Ohmic dissipation. Applying the fluctuation-dissipation theorem, we generalize the Johnson-Nyquist formula for thermoelectrics, finding an enhanced voltage fluctuation spectral density 4 k B T R (1 +  Z D T ) at frequencies below a thermal cut-off frequency f T, where Z D T is the dimensionless thermoelectric device figure of merit. The origin of the enhancement in voltage noise is thermoelectric coupling of temperature fluctuations. We use a wideband, integrated thermoelectric micro-device to experimentally confirm our findings. Measuring the Z D T enhanced voltage noise, we experimentally resolve temperature fluctuations with a root mean square amplitude of at a mean temperature of 295 K. We find that thermoelectric devices can be used for thermometry with sufficient resolution to measure the fundamental temperature fluctuations described by the fluctuation-dissipation theorem.